ShinyWYSIWYG: a Shiny What You See Is What You Get editor - Rodriguez, Juan C. (2018)
For any computer application, having a graphical user interface (GUI) potentially increases its usability and scope. In the case of the R language, one of the most used alternatives is the Shiny [1] library. Shiny is an R package that facilitates the creation of interactive web applications directly from R. However, using Shiny requires a certain level of knowledge of R programming. Looking at CRAN’s Task Views, it is easy to note that the R community brings together a variety of specialists in various fields such as biologists, agronomists, economists, among others. It is therefore crucial that R development tools maximize the level of programmatic simplicity to ease the start of the learning ramp. In order to further facilitate the process of developing a user-friendly GUI, and tackling this learning gap, here we present the ShinyWYSIWYG application. ShinyWYSIWYG is a visual editor that allows the user, using the drag and drop technique, inserting the various fields that Shiny provides as input and output, by selecting the desired size and position for each field. Once the user interface is generated, ShinyWYSIWYG also eases the development of the server logic.